Keterlibatan Manajemen Pengetahuan dan Manajemen Bakat Pada Kinerja Karyawan di PT Ditoeku - Roymon Panjaitan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
The goal of this study is to further discuss the participation of knowledge management and talent management in enhancing employee performance. The study used in quantitative method amounted to 55 employees at PT Ditoeku as respondents. Data collection instruments are conducted through the dissemination of questionnaires, surveys, interviews, and literature study support. Analyze data processing with descriptive analysis and linear regression for further hypothesis development. The research showed that information factors have a significant positive influence on employee in part and that some talent management has a significant positive effect on employee.. This correlation relationship has two positive contributions, the first practically implicating the managerial of the company that can directly improve the performance of employees from employee talent, both real knowledge management can improve employee performance that impacts the individual and for the company.